Hydroboration of Terminal Olefins with Pinacolborane Catalyzed by New Mono(2-Iminopyrrolyl) Cobalt(II) Complexes - Cruz, Tiago F C; Lopes, Patrícia S; Pereira, Laura C J; Veiros, Luís F; Gomes, Pedro T (Inorganic chemistry, 2018)
The 5-substituted 2-aryliminopyrrolyl ligand precursors of the type 5-R-2-[ N-(2,6-diisopropylphenyl)formimino]-1 H-pyrrole (R = 2,6-Me -C H (1a), 2,4,6- Pr -C H (1b), 2,4,6-Ph -C H (1c; reported in this work), anthracen-9-yl (1d), CPh (1e; reported in this work)) were treated with K[N(SiMe ) ] in toluene to yield the respective 5-R-2-[ N-(2,6-diisopropylphenyl)formimino]pyrrolyl potassium salts 2a-e in high yields. The paramagnetic 15-electron Co(II) complexes of the type [Co{κ N,N'-5-R-NC H -2-C(H)═N(2,6- Pr -C H )}(Py)Cl] (3a-e; Py = pyridine) were prepared by salt metathesis of CoCl (Py) with the respective potassium salts 2a-e in moderate to good yields. When the CoCl (THF) precursor was combined with the in situ prepared sodium salt of ligand precursor 1b, the trinuclear complex [Co{κ N, N'-5-(2,4,6- Pr -C H )-NC H -2-C(H)═N(2,6- Pr -C H )}(μ-Cl)] [(μ-Cl) Co(THF) ] (4) was obtained in high yields. Complexes 3a-e have high-spin electronic configurations both in solution and in the solid state. X-ray diffraction studies of complexes 3a,e confirmed distorted tetrahedral coordination geometries. Complex 4, on the other hand, is a linear trinuclear Co(II)-Co(II)-Co(II) complex with two terminal distorted tetrahedral four-coordinate sites and a central octahedral six-coordinate site, all in the high-spin state, S = 3/2, as confirmed by the magnetization measurements and DFT calculations. Solid-state magnetic measurements in both complexes 3a and 4 point to paramagnetic behavior with a significant contribution of spin-orbit coupling. Additionally, intramolecular antiferromagnetic coupling of the adjacent cobalt atoms is observed in 4. The Co(II) family 3a-d, on activation with K(HBEt ), catalyzed the hydroboration of several α-olefins with pinacolborane, in good to high yields (50-80%). This system almost exclusively yielded the anti-Markovnikov (a-Mk) addition product, except when styrene was used, where the selectivity in the Markovnikov (Mk) product increased with increasing steric bulkiness of the 5-R-2-iminopyrrolyl substituent, with the a-Mk:Mk molar ratio varying from 2.33:1 (3a, R = 2,6-Me -C H ) to 0.75:1 (3c, R = 2,4,6-Ph -C H ). Preliminary mechanistic studies indicate that the activation by K(HBEt ) gave rise to a Co(I) species, the catalyst system likely following an oxidative addition pathway.